Assessment of a radioisotopic assay for vitamin B12 using an intrinsic factor preparation with R proteins blocked by vitamin B12 analogues. Issue 10 (October 1982) - Bain, Barbara; Broom, GN; Woodside, Jackie; Litwinczuk, RA; Wickramasinghe, SN
Abstract : A competitive protein binding radioassay kit for serum vitamin B12 has been assessed. Precision, linearity, sensitivity, and specificity have been found to be satisfactory. Falsely-normal assay results in patients with vitamin B12 deficiency have not been observed.